2018
DOI: 10.1007/s10865-018-9967-y
|View full text |Cite
|
Sign up to set email alerts
|

Sleep quality buffers the effects of negative social interactions on maternal mood in the 3–6 month postpartum period: a daily diary study

Abstract: Sleep and social relationships are two key determinants of psychosocial health that undergo considerable change across the transition to motherhood. The current study investigated the bidirectional relationship between daytime Positive and Negative Social Interactions (PSIs & NSIs) and nighttime sleep quality on maternal mood across 1 week in the 3-6 month postpartum period. Sixty healthy, non-depressed first-time mothers completed 7-consecutive days of daily social interaction and sleep diaries. Results indic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 73 publications
0
10
0
Order By: Relevance
“…While the subscales do provide utility, some researchers may still opt to use the aggregate positive or negative affect subscales as has been done in past research (e.g. Cohen et al, 2003Cohen et al, , 2006Jenkins et al, 2018;Lillis et al, 2018;Poole et al, 2011;Sultan & Fisher, 2010). The findings suggest that the items from the SAS do load on to two unique factors (negative and positive affect).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…While the subscales do provide utility, some researchers may still opt to use the aggregate positive or negative affect subscales as has been done in past research (e.g. Cohen et al, 2003Cohen et al, , 2006Jenkins et al, 2018;Lillis et al, 2018;Poole et al, 2011;Sultan & Fisher, 2010). The findings suggest that the items from the SAS do load on to two unique factors (negative and positive affect).…”
Section: Discussionmentioning
confidence: 96%
“…Investigations using the overall negative affect scale find that higher negative affect is associated with greater flu/cold symptoms (Cohen et al, 2003(Cohen et al, , 2006, higher disease severity in individuals with Type 2 diabetes (Sultan & Fisher, 2010), and lower sleep quality (Lillis et al, 2018). Similarly, studies using the overall positive affect scale find associations in the expected directions, with greater positive affect being associated with better sleep quality (Lillis et al, 2018) and more physical activity (Poole et al, 2011). Further, studies utilising the subscales find more nuanced effects.…”
mentioning
confidence: 98%
“…Worse sleep quality, for example, is related to both heart disease in the adult population (Cappuccio et al 2011) and depression among parents (Park, Meltzer-Brody, and Stickgold 2013). Poor sleep quality is associated with more harsh parenting behavior (Kelly et al 2021), and worse daily sleep quality has been found to exacerbate the effects of chronic and daily stressors on daily negative parental mood (da Estrela et al 2018;Lillis et al 2018;Mihaila and Hartley 2018). Thus, improvements in sleep quality may have the potential to lead to longer-term improvements in family functioning and child well-being, such as more positive parent-child interactions, reduced parental stress, and improved child behavior.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the physiological dysregulation associated with insomnia or sleep disturbance results in psychological problems, such as depression, which cause individuals to be withdrawn from networking activities (Maier & Watkins, 1998). More specifically, poor sleep has always been shown to disrupt efforts to regulate emotion (Lillis et al, 2018), amplifying negative emotions in response to unpleasant events and reducing positive responses to pleasant ones (Dov et al, 2005). Some researchers argued that sleep quality is one of the root causes of depression in older adults (Zhang et al, 2020).…”
Section: Health Mechanism In the Relationship Between Sleep Quality And Pssmentioning
confidence: 99%